The use of social media to learn English: A perspective of cadets of the Port and Shipping Management Department - Yozar Firdaus Amrullah; Fatimah Fatimah; Latifa Ika Sari (Jurnal CULTURE (Culture, Language, and Literature Review), 2024)
Advances in information technology have led to significant changes in the teaching and learning process, enabling traditional face-to-face methods to be replaced or supplemented by online meetings. Social media, designed initially for social interaction and entertainment, has increasingly become a tool for sharing educational content, including language learning. While prior studies have demonstrated the potential of social media for academic purposes, there is a gap in research focusing on maritime cadets' use of social media for learning English. This study examines cadets’ perspectives in the Port and Shipping Management department on using social media for English learning. This research employs a descriptive qualitative approach. Data was collected via online surveys. Among the 89 respondents, all were active social media users, and 85 reported using these platforms, primarily Instagram, YouTube, and TikTok, for language learning. The cadets expressed interest in developing speaking, reading, writing, and listening skills. However, the study also identified challenges, including internet connectivity issues and entertainment content distractions. These findings suggest that while social media provides valuable language learning resources, obstacles must be addressed to optimize its effectiveness as an educational tool. English lecturers can combine learning in class by utilizing content provided by existing social media accounts.